A brilliant madness : living with manic-depressive illness - Duke, Patty, 1946-2016 (Bantam Books, 1993)
Actress Patty Duke recounts her experiences as a manic-depressive. Gloria Hockman reports on latest findings on the probable causes and treatments of the illness.